PENGARUH KUALITAS PRODUK, BRAND IMAGE DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA PRODUK KOSMETIK WARDAH - YOLA NOVIANTI; TIURNIARI PURBA (LP2MTBM MAKARIOZ, 2020)
The business world today is characterized by increasingly fierce competition, specifically to provide satisfaction and retaincustomers. In marketing to overcome the intense competition, efforts that must be carried out by companies includeincreasing product quality, building a strong brand image and improving service quality. This research was conducted aimingto determine the effect of Product Quality, Brand Image and Service Quality on Consumer Satisfaction in Wardah CosmeticProducts. The sample technique is using purposive sampling, and the sample taken is 100 respondents using the Slovinformula. The research tool used a questionnaire and then tabulated and continued to be analyzed using descriptive analysis,hypothesis testing using multiple linear regression analysis test, determination test, t test and f test with the help of SPSSversion 22. Variable product quality effect of 25.9% and positive value and significant. The brand image variable has aneffect of 21.5% and is positive and significant. Variable service quality has an effect of 18.2% and is positive and significant.Product quality, brand image and service quality have a positive and significant effect with the effect value of 37.3% and thecalculated F value of 19.051> 2.70 F table, the probability value of 0.000 <0.05 alpha. Product quality variable gives adominant influence of 25.9%.